Inter-cultural communication at work cultural values in discourse - Clyne, Michael G. 1939-2010 (Cambridge Univ. Pr., 1994)
In this interdisciplinary study, Professor Clyne examines the impact of cultural values on discourse. Through an exploration of the role of verbal communication patterns in successful and unsuccessful communication, he sets out to integrate and develop a framework for a linguistics of inter-cultural communication. Professor Clyne draws on data derived from recordings of spontaneous communication in the Australian workplace between people of vastly differing backgrounds, notably European and Asian, who use English as a lingua franca. This study offers both a pragmatics and a discourse perspective, not simply analysing data, but seeking to extend the theoretical model. The rapidly increasing use of English as a language of inter-cultural communication between non-native speakers means that the issues raised here will be of interest not only to linguists, but also to those involved in education, business, and industry.
Keywords: Actes de parole; Analyse du discours; Communication interculturelle; Discourse analysis; Engels; Interculturele communicatie; Langage et culture; Englisch; Interkulturelle Kommunikation; Intercultural communication; Language and culture; Speech acts (Linguistics); Soziolinguistik; Verkehrssprache; Arbeitswelt; Sprache; Kommunikation; Kulturkontakt; Konversationsanalyse